Extraction and characterization of hardness causing minerals present in tap water to study its adsorption and catalysis - Singla, Deepak (My University, 2018)
The present work describes the extraction and characterization of hardness causing minerals obtained from tap water boiling (TWB). The extracted residues were centrifuged (8000 rpm, 5 min, 25oC) and washed three times with water, ethanol, respectively. Later on, it was dried at room temperature. The powder form of this residue (RMP-TWB) was further sintered at 400oC and 900oC for 4 h in the furnace. It was characterized by using DLS, XRD, SEM, FTIR, BET and UV- Visible spectroscopy techniques etc. Then this powder was used to investigate its adsorption and photocatalytic properties for removal and degradation of Malachite Green (MG) dye under a sunlight irradiation. DLS measurements showed that the particle size distribution of RMP-TWB lies in the range between from 0.163 µm to 726 µm. XRD data revealed that RMP-TWB contains the majority of the calcium carbonate (CaCO3) and some amount of MgO, SiO2 etc. The surface morphology of residue showed the sphere, rod-like shapes and the particle size lies between 1µm to 10µm. From BET and BJH analysis, the surface area and mean pore diameter of RMP-TWB was found to be 35.4m2g-1 and 10.08 nm, respectively. The impact of different parameters likes concentration of MG dye; the amount of adsorbent on adsorption was also studied. The adsorption curve follows the Freundlich adsorption isotherm. The degradation of MG dye under sunlight irradiation was studied at different intervals of time and measured its kinetics studies by zero and first order reaction. The results showed that after 60 to 90 min sunlight irradiation maximum degradation of MG dye was observed. It was concluded that this hardness causing minerals will be very effective for adsorption, removal, and degradation of toxic industrial MG dye in the presence of sunlight.
Keywords: Extraction residues from tap water; CaCO3; MgO; SiO2 Malachite; Adsorption study; Photocatalytic degradation